Trends in disability-free life expectancy in the United States, 1970-90 - Crimmins, E. M.; Saito, Y.; Ingegneri, D.
tbls., gráfs.
pp. 555-572
Keywords: Promedio de Vida; Aspectos Demograficos; Mortalidad; Calidad de la Vida; Estados Unidos de America